Changes in attitudes towards smoking during smoking cessation courses for Turkish- and Albanian-speaking migrants in Switzerland and its association with smoking behavior: A latent change score approach - Paz Castro, Raquel; Henninger, Mirka; Schaub, Michael P.; Salis Gross, Corina (Frontiers in Psychology, 2022)
Introduction: Migrant populations usually report higher smoking rates than locals. At the same time, people with a migration background have little or no access to regular smoking cessation treatment. In the last two decades, regular smoking cessation courses were adapted to reach out to Turkish- and Albanian-speaking migrants living in Switzerland. The main aims of the current study were (1) to analyze the effects of an adapted smoking cessation course for Turkish- and Albanian-speaking migrants in Switzerland on attitudes towards smoking and smoking behavior; and (2) to elucidate whether changes in attitudes towards smoking were associated to changes in smoking behavior in the short- and in the long-term. Methods: A total of 59 smoking cessation courses (Turkish: 37; Albanian: 22) with 436 participants (T: 268; A: 168) held between 2014- 2019 were evaluated. Attitudes towards smoking and cigarettes smoked per day were assessed at baseline and three-months follow-up. One-year follow-up calls included assessment of cigarettes smoked per day. Data were analysed by means of structural equation modelling with latent change scores. Results: Participation in an adapted smoking cessation course led to a decrease of positive attitudes towards smoking (T: β = -.65, p<.001; A: β = -.68, p<.001) and a decrease of cigarettes smoked per day in the short-term (T: β = -.58, p<.001; A: β = -.43, p<.001) with only Turkish-speaking migrants further reducing their smoking in the long-term (T: β = -.59, p<.001; A: β = -.14, p=.57). Greater decreases in positive attitudes were associated with greater reductions of smoking in the short-term (T: r = .39, p<.001; A: r = .32, p=.03), but not in the long-term (T: r = -.01, p=.88; A: r = -.001, p=.99). Conclusion: The adapted smoking cessation courses fostered changes in positive attitudes towards smoking that were associated with intended behavior change in the short-term. The importance of socio-cognitive characteristics related to behavior change maintenance to further increase treatment effectiveness in the long-term is discussed.